2015
DOI: 10.1007/s11126-015-9350-x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery, as Experienced by Women with Borderline Personality Disorder

Abstract: Studies examining recovery through the service users' perspectives have mainly included persons with schizophrenia or bipolar disorder. Giving voice to those with borderline personality disorder (BPD) would enrich our understanding of recovery, as their specific experiences may bring new dimensions, obstacles and facilitators. The objective of this study was to qualitatively capture the experience of recovery in women with BPD. Participants were women between 18 and 65 years old who had a diagnosis of BPD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 18 publications
4
37
0
Order By: Relevance
“…These views are inconsistent with qualitative research by Larivière et al. (), which suggested that involvement in meaningful activities such as employment and education was a key dimension of recovery in borderline personality disorder for patients themselves. The views expressed by staff in the present study perhaps indicate that they do not expect that patients with borderline personality disorder are capable of engaging with these activities or achieving ‘normal’ functioning.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…These views are inconsistent with qualitative research by Larivière et al. (), which suggested that involvement in meaningful activities such as employment and education was a key dimension of recovery in borderline personality disorder for patients themselves. The views expressed by staff in the present study perhaps indicate that they do not expect that patients with borderline personality disorder are capable of engaging with these activities or achieving ‘normal’ functioning.…”
Section: Discussionmentioning
confidence: 67%
“…A recent systematic review by Ng, Bourke, and Grenyer () aimed to understand how patients, clinicians, family, and carers perceived recovery from borderline personality disorder. The review identified 16 longitudinal quantitative studies with 11 unique cohorts, and three qualitative studies (Larivière et al., ; Katsakou et al., ; Holm & Severinsson, ) that examined recovery in borderline personality disorder. Quantitative studies tended to define recovery in terms of clinical remission from diagnostic criteria, and level of functioning as measured through scales such as the Health‐Sickness Rating Scale (Luborsky, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Job environment can be one of the areas where patients with BPD struggle for maintaining their identity. 46 – 49 Conflicts with boss and colleagues are frequent; individuals with BPD mostly fight against assumed injustice and nepotism and accuse the others of incompetence, lack of diligence, and gaining benefits from their bosses. Occupational patterns are characterized by instability, intense preoccupation, the subsequent loss of interest in the job, lack of job satisfaction, and problems in relationships.…”
Section: Introductionmentioning
confidence: 99%
“…The findings in this study tend to point to an overall lack of meaning in the activities accomplished and this justifies the importance of client-centred interventions to better understand the values, the interests and the types of meaning derived from activities experienced by clients with personality disorders and then, to enable accomplishment of meaningful activities in their daily life considering facilitators and obstacles. This was identified as a dimension of recovery in persons with borderline personality disorders [42,43]. As both groups of women felt imbalanced in every category of needs assessed in the subjective life balance questionnaire, it would be useful to provide opportunities and tools, such as the Life Balance Inventory or the Occupational Questionnaire, to reflect on use of time and on quantity and variety of activities one experiences in order to improve overall global health and quality of life.…”
Section: Resultsmentioning
confidence: 99%